The Effect of the Separation of Spermatozoa X and Y Using Swim up Method on the Quality of Etawah Crossbreed Goats Spermatozoa - Eskayanti Pasaribu; Dasrul Dasrul; Ginta Riady (Universitas Syiah Kuala, 2014)
This research aimed to determine the effect of spermatozoa X and Y separation using swim-up method on the quality of etawah crossbreed goat’s spermatozoa. This research used 6 male etawah crossbreed goats aged between 18-24 months, which were collected the semen once a week using electroejaculator. Immediately after semen collection, the quality of semen was examined, and then grouped into three treatment groups. Group 1 was control group (P0) refers to the semen was not separated by swim-up method. Group 2 (P1) was the semen separated by the swim-up method for 5 minutes. Group 3 (P2) was the semen separated by swim-up method for 10 minutes. Each treatment was repeated six times. Parameters for semen quality examined were the percentage of spermatozoa motility, live spermatozoa, and abnormal spermatozoa. Data were analyzed by analysis of variance (ANOVA) one way pattern, followed by Duncan's multiple test. The results showed that the mean ± SD percentage of sperm motility on each treatment groups (P0; P1; P2) was 81.33±3.44, 89.67±3.21, and 90.00±3.10 %, respectively. The percentage of live spermatozoa on each group was 86.50 ± 2.07, 92.33 ± 2.08, and 91.83 ± 1.72%, respectively. The percentage of abnormal spermatozoa on each group was 13.00±2.53, 7.33±2.52, and 7.67±2.16%, respectively. Results of this research showed that the percentages of motility, live spermatozoa, and abnormal spermatozoa after separation by swim-up method were significantly different (P0.05) compared to without separation. It can be concluded that the separation of spermatozoa using swim-up method can improve significantly (P0.05) the percentage of live and motility of spermatozoa and decrease the percentage of abnormal spermatozoa of etawah crossbreed goats.Key words: Etawah crossbreed, spermatozoa quality, swim-up method